Open Days Kröller-Müller Museum. - Barnas, Maria; Brassinga, Anneke; Bruinja, Tsead; Duinker, Arjen; Gerbrandy, Piet; Langelaar, Marije; Mandelinck, Gwy; Manders, Mark; Nolens, Leonard; Ohlsen, Ronald; Pfeijffer, Ilya Leonard; Puthaar, René; et al. (Amsterdam Amsterdam : Roma Publications, 2002)
Borremans, Michaël ; Süter, Batia ; Hirakawa, Noritoshi ; Herrara, Arturo ; Manders, Mark ; Langelaar, Marije ; Braeckman, Dirk ; Tuymans, Luc ; Willems, Roger ; van Riessen, Wouter ; Kahrs, Johannes ; Strba, Annelies
Nederlands
Open Days Kröller-Müller Museum, Kröller-Müller Museum, Otterlo, 30/11/02 - 12/1/03
boek